Decision to Work in the Formal and Informal Sector: Empirical Evidence from East Java Province - Siti Munawaroh (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
This study examines individual determinants of entering employment in the formal and informal sectors in East Java Province. This study uses the 2014 Indonesian Family Life Survey (IFLS) (wave 5) microdata. The analysis used in this study is logistic regression analysis. The results of this study indicate that the level of education as measured by years of schooling and wages has a significant positive effect on the decision of workers to work in the formal and informal sectors. It means that individuals with higher levels of education and high wages have a greater tendency to work in the formal sector than in the informal sector.